2015
DOI: 10.1074/jbc.m115.659680
|View full text |Cite
|
Sign up to set email alerts
|

Human γ-Glutamyl Transpeptidase 1

Abstract: Background: ␥-Glutamyl transpeptidase 1 (GGT1) plays a role in asthma, reperfusion injury, and cancer. Results: We report four new crystal structures of human GGT1, including the free enzyme, inhibitor-bound transition states, and glutamate-bound enzyme. Conclusion: Novel enzyme-substrate interactions and movement of the catalytic nucleophile, oxyanion hole, and lid loop were revealed. Significance: This structural information is critical for developing GGT1 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…As an anti-oxidative enzyme, GGT plays an important role in the cancer cell under stress [8]. It has been reported that GGT elevation is accompanied by an increased invasive behavior in melanoma and breast cancer, which is in accordance with our results [16, 22].…”
Section: Discussionsupporting
confidence: 92%
“…As an anti-oxidative enzyme, GGT plays an important role in the cancer cell under stress [8]. It has been reported that GGT elevation is accompanied by an increased invasive behavior in melanoma and breast cancer, which is in accordance with our results [16, 22].…”
Section: Discussionsupporting
confidence: 92%
“…Sensitivity for GGT activity may be improved with more reactive or better polarizing probes,o rw ith optimized formulations for polarization. Inset spectra:sum of individual scans containing HP signal (scans [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Gly (20 mm)w ith kidney homogenate from rats treated or untreated with the GGT inhibitor acivicin (0 or 10 mg kg À1 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[2b] GGT has been implicated in the development and progression of malignant tumors,w here its elevated expression increases the availability of cysteine for intracellular GSH production, limiting damage from oxidative stress and facilitating GSH-dependent drug resistance mechanisms. [4] GGT requires substrates bearing a g-glutamyl moiety but accommodates ar ange of substituents at the g-position (Figure 1a), [5,6] providing astrategy for the design of molecular probes targeting GGT.A fluorogenic probe activated upon cleavage by GGT may be useful to identify GGT-expressing tumors during surgical resection. [3] GGT may therefore serve as at umor biomarker and its presence on the cell surface is particularly attractive for imaging applications.Recently,reagents capable of detecting the presence of GGT in vivo using fluorescence or radioactivity have been described.…”
mentioning
confidence: 99%
“…[3] GGT may therefore serve as at umor biomarker and its presence on the cell surface is particularly attractive for imaging applications.Recently,reagents capable of detecting the presence of GGT in vivo using fluorescence or radioactivity have been described. [4] GGT requires substrates bearing a g-glutamyl moiety but accommodates ar ange of substituents at the g-position (Figure 1a), [5,6] providing astrategy for the design of molecular probes targeting GGT.A fluorogenic probe activated upon cleavage by GGT may be useful to identify GGT-expressing tumors during surgical resection. [4a] This particular application avoids the problem of tissue opacity often encountered with fluorescent probes.…”
mentioning
confidence: 99%